Using a period incidence survey to compare antibiotic use in children between a university hospital and a district hospital in a country with low antimicrobial resistance: a prospective observational study. Issue 5 (27th May 2019) - Thaulow, Christian Magnus; Blix, Hege Salvesen; Eriksen, Beate Horsberg; Ask, Ingvild; Myklebust, Tor Åge; Berild, Dag
Abstract : Objectives: To describe and compare antibiotic use in relation to indications, doses, adherence rate to guidelines and rates of broad-spectrum antibiotics (BSA) in two different paediatric departments with different academic cultures, and identify areas with room for improvement. Design: Prospective observational survey of antibiotic use. Setting: Paediatric departments in a university hospital (UH) and a district hospital (DH) in Norway, 2017. The registration period was 1 year at the DH and 4 months at the UH. Participants: 201 children at the DH (mean age 3.8: SD 5.1) and 137 children at the UH (mean age 2.0: SD 5.9) were treated with systemic antibiotics by a paediatrician in the study period and included in the study. Outcome measures: Main outcome variables were prescriptions of antibiotics, treatments with antibiotics, rates of BSA, median doses and adherence rate to national guidelines. Results: In total, 744 prescriptions of antibiotics were given at the UH and 638 at the DH. Total adherence rate to guidelines was 75% at the UH and 69% at the DH (p=0.244). The rate of treatments involving BSA did not differ significantly between the hospitals (p=0.263). Use of BSA was related to treatment of central nervous system (CNS) infections, patients with underlying medical conditions or targeted microbiological treatment in 92% and 86% of the treatments, at the UH and DH, respectively (p=0.217). A larger proportion of the children at the DH were treated for respiratory tract infections (p<0.01) compared with the UH. Children at the UH were treated with higher doses of ampicillin and cefotaxime (p<0.05) compared with the DH. Conclusion: Our results indicate that Norwegian paediatricians have a common understanding of main aspects in rational antibiotic use independently of working in a UH or DH. Variations in treatment of respiratory tract infections and in doses of antibiotics should be further studied.